Autoimmune Encephalitis: Diagnostic Biomarkers and Advances in Immunotherapy - Rasheed, Sadam Hameed; Mohamed, Noora khallifah; Alobaidi, Naseer Khaleel; Mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2025)
Autoimmune encephalitis (AE) represents a rapidly growing field of neuroimmunology, characterized by an immune-mediated attack on neuronal cell surface or synaptic antigens. Over the past decade, substantial progress has been made in understanding its pathophysiology, leading to the identification of a range of diagnostic biomarkers that have revolutionized early detection and treatment. Clinically, AE often presents with subacute onset of psychiatric symptoms, cognitive decline, seizures, and movement disorders, frequently mimicking infectious or primary psychiatric conditions. The detection of specific neuronal autoantibodies, such as those against N-methyl-D-aspartate receptor (NMDAR), leucine-rich glioma-inactivated 1 (LGI1), contactin-associated protein-like 2 (CASPR2), and γ-aminobutyric acid (GABA) receptors, has emerged as a cornerstone in diagnosis. These biomarkers not only aid in differentiating AE from other encephalopathies but also provide insights into disease mechanisms and prognosis. Advances in neuroimaging, particularly MRI and FDG-PET, combined with cerebrospinal fluid analysis, further enhance diagnostic accuracy. Importantly, immunotherapy has transformed the management of AE. First-line therapies, including corticosteroids, intravenous immunoglobulin, and plasma exchange, often yield substantial improvement, while second-line agents such as rituximab and cyclophosphamide are employed in refractory cases. Novel approaches targeting B cells and complement pathways are currently under investigation, offering promise for more tailored interventions. Early recognition and treatment are crucial, as delays significantly impact long-term neurological outcomes. This review highlights the evolving landscape of AE, emphasizing the role of biomarkers in guiding diagnosis and monitoring, as well as recent advances in immunotherapy that have significantly improved prognosis and patient quality of life.